The Effect of Different Ratio of Methionine-Zinc and Zinc Oxide on Performance Indicators and Diarrhea in Suckling Holstein Calves - Morteza Rezapour; Yadollah Chashnidel; Asadollah Teimoury Yansary; Essa Dirandeh (پژوهشهای علوم دامی ایران)
Introduction[1]: Diarrhea is the main cause of calf mortality in the first two weeks after birth. Even when calves recover from diarrhea, they may subsequently show impaired growth. Considering this fact and especially following the ban of antibiotics in many countries, it is very important to identify effective anti-diarrheal supplements for use in suckling calves. Zinc is an effective anti-inflammatory and anti-diarrheal substance that improves the function of the immune system, reduces the number of pathogenic bacteria and increases the relative abundance of beneficial microbes in the digestive system. It is thought that the mechanisms of anti-diarrheal effect of zinc element are due to regulation of intestinal fluid transfer and mucosal integrity, strengthening of immunity and modulation of oxidative stress. The purpose of this experiment is to investigate the use of different proportions of organic (methionine-zinc) and inorganic (zinc oxide) sources of zinc to prevent diarrhea, improve the condition of the immune system and performance indicators of suckling calves. Materials and Methods: A total of 50 suckling Holstein calves were used over 70 days in a completely randomized design with 5 treatments and 10 replications. The experimental treatments were different proportions of organic and inorganic zinc supplements, including 1) zinc supplementation, 100% Methionine-zinc 2) combination of 75% methionine-zinc and 25% zinc oxide, 3) combination of 50% methionine-zinc and 50% zinc oxide, 4) combination of 25% methionine-zinc and 75% zinc oxide, and 5) 100% zinc oxide. All treatments received 1.96 mg of zinc supplementation per kilogram of body weight. Zinc supplements mixed with milk were fed to the calves from day one to day 14, and performance monitoring continued for 70 days. The stool score was evaluated on a scale of 1 to 4. Diarrhea was defined as the presence of grade 3 or 4 stools for 2 consecutive days. Data were analyzed in a completely randomized design using the GLM procedure of SAS. For variables measured over time (average daily gain, dry matter intake, and feed conversion ratio), time was added to the model as a repeated factor. Results and Discussion: The results showed that experimental treatments did not significantly effect the average daily gain, dry matter intake, and feed conversion ratio of the calves fed with Different ratios of mineral (zinc oxide) and organic (methionine-zinc) sources of zinc. In addition, the average of fecal consistency score did not differ significantly among the treatments. The results blood analysis demonstrated that treatment 100% methionine-zinc had higher level of concentration alkaline phosphatase. However, among the treatments contained methionine-zinc, a decrease in the ratio of methionine-zinc resulted in a decrease in Alkaline phosphatase concentration. Higher ratios of zinc oxide caused a significant decrease in the concentration of superoxide dismutase in the blood on the 14th and 70th day of the experiment. Also, on the 70th day of the test, the antioxidant capacity of whole blood was significantly higher in treatments containing methionine-zinc than in treatment %100 zinc oxide. The results showed that other blood parameters were not significantly influenced by the treatments in this study. In general, production performance did not change in different ratios of organic and mineral sources, the lack of effect of replacing zinc oxide with methionine-zinc on the performance of the present calves may be due to the provision of sufficient levels of zinc for all calves. So that the zinc supplement, taking into account its purity percentage, reached the same amount (1.96 mg of zinc supplement per kilogram of body weight) in all treatments. Conclusion: In the present study, overall production performance and blood parameter concentrations did not change with different ratios of organic and mineral sources. However, the activity of antioxidant enzymes was higher with higher ratios of the organic supplement (methionine-zinc) compared to the mineral source (zinc oxide). The lack of positive effect of replacing zinc oxide with methionine-zinc on the performance of the present calves may be due to the provision of sufficient levels of zinc for all calves. And it can be said that when a mineral is supplied at a sufficient level, the chemical form and bioavailability of resources are less important on performance.